Manajemen Pembelajaran Daring Pendidikan Anak Usia Dini di Masa Pandemi Covid-19 (Studi Kasus TK Fullday School Hadlonah Darussalam Gontor Ponorogo - Aynun Nurul Ulufah; Muhammad Thoyib (Pascasarjana IAIN Ponorogo, 2022)
To prevent the spread of the corona virus, educational institutions organize distance learning. Inthe online learning process so far, teachers and students as well as parents experience many problems, so online learning is considered less effective. In such circumstances, an effective learning solution is needed in planning, implementing and evaluating online learning. The purpose of this study is to explain, describe and analyze the planning, implementation and evaluation of online learning during the Covid-19 pandemic. The researcher uses a qualitative approach. Data collection techniques using interviews, observation and documentation. To analyze the research data, the Miles and Huberman model that the researcher uses as a reference. The results showed that: 1) Online learning planning for PAUD during the COVID-19 pandemicat Hadlonah Darussalam Kindergarten is a routine activity at the beginning of each semester, where the planning results include RPPS, Syllabus, RPPM, and online RPPH; 2) Implementation of online learning in Hadlonah Kindergarten using the WhatsApp application. The material is delivered through tutorials in WhatsApp Groups such as voicenotes, video recordings, youtube. The strategies used by TK are online and offline; 3) Evaluation of online learning of Hadlonah Darussalam Kindergarten is taken from observing assignments (photos, videos and voice recordings) and seeing the performance of students. The learning evaluation shows that the online learning interaction process is more effective, due to the effective use of the Whatsaap application as a means of communication between teachers and students.